Analisis Pendapatan dan Optimalisasi Penggunaan Faktor Produksi Usahatani Padi Sawah di Gapoktan Tio Olami Desa Bongoime Kecamatan Tilongkabila Kabupaten Bone Bolango - Cici Djafar; Asda Rauf; Ramlan Mustafa (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2023)
The role of the agricultural sector, in reality, significantly contributes to the provision of food, income, and other goods. This contribution significantly impacts Indonesia's economy from year to year, especially the income of farmers who cultivate agricultural products in pursuit of a farmer's well-being. One of the agricultural efforts that play a crucial role in meeting the dietary needs of the Indonesian population, where rice serves as a staple food, is paddy farming. The execution of this research aims to achieve two objectives to determine the production costs, revenues, and income of paddy farming in Bongoime Village, Tilongkabila District, Bone Bolango Regency, and to conduct an analysis on the optimal usage of production inputs in paddy farming grown and cultivated in Tilongkabila District, Bongoime Village, Bone Bolango Regency. Based on the research objectives, the researcher employed a method to facilitate the research, which is through the use of a survey method and direct quantitative analysis techniques. All the data collected during the research, including costs, revenues, income, and the optimization of the usage of production factors, were analyzed. The findings indicate that the average cost per farmer and harvest is Rp. 4,124,030.87. Meanwhile, the average net income per farmer per harvest is Rp. 17,696,268, and the average income per farmer per harvest is Rp. 21,820,298.51. Land use and pesticide usage for production have not reached an optimal level, thus efforts to reduce usage are necessary to increase production, as indicated by the analysis of input production optimization. Regarding the use of certain production inputs, such as seeds, urea fertilizer, phonska fertilizer, and labour, they remain at a suboptimal level. This indicates the need for increased usage to enhance production.